Representação e construção de género na peleja brasileira - Carlos Nogueira; John Rex Amuzu Gadzekpo (Caravelle)
In this article, through an analysis of forms and contents of several Brazilian pelejas, selected from many hundreds of cordel leaflets, we try to show how they present men and women and place them in a conflict often ending in a fight or quarrel; and we try to understand the place of this textual genre in the (re)construction of Brazilian society (and its role elsewhere as well).